Education, leadership and Islam theories, discourses and practices from an Islamic perspective - Shah, Saeeda (Routledge research in education, 2016)
Education, Leadership and Islam focuses on contemporary educational settings and practices, drawing on research and empirical evidence from multicultural contexts in order to enrich theory and inform policy and practice in relevant frameworks, particularly in relation to the growing Muslim population in the West. This book offers critical insight into educational theory and practice, and as such will be key reading for policy makers and educational leaders.